The relationships between language learning strategies and positive emotions among Malaysian ESL undergraduates - Mohammadipour, Mohammad; Md Rashid, Sabariah; Rafik-Galea, Shameem; Yap, Ngee Thai (Australian International Academic Centre, 2018)
Emotions are an indispensable part of second language learning. The aim of this study is to determine the relationship between the use of language learning strategies and positive emotions. The present study adopted a sequential mixed methods design. The participants were 300 Malaysian ESL undergraduates selected through stratified random sampling from 5 public universities in Malaysia. The quantitative data were collected through two sets of questionnaires: (a) Oxford’s (1990) Strategy Inventory for Language Learning (SILL), and (b) Fredrickson’s (2009) modified Differential Emotional Scale (mDES). The qualitative data were gathered through semi-structured interviews. With regard to the quantitative data analysis, a series of t-tests and correlational analyses were used. The data from the interviews were analysed qualitatively. A positive significant correlation was found between positive emotions and overall language learning strategy use. Also, the qualitative results of the study indicated that the learners who experienced more positive emotions tended to use a greater variety of language learning strategies. The findings of the study emphasise the importance of students’ positive emotions in their use of language learning strategies. It might be suggested that teachers by designing the classroom settings and instructions which promote positive emotions can inspire learners to use language learning strategies more frequently and with a greater variety which in sequence relate to learners’ language learning proficiency.